Ekonomi Politik, Internet, dan Demokrasi - Ferdinandus - Jehalut (Jurnal Ledalero, 2023)
This article aims to explain the political economy of the Internet and its relevance to democracy. Thiselaboration is an alternative to the utopian and dystopian techno-determinist approaches in viewing the relationshipbetween the Internet and democracy. From a political economy perspective, the Internet and its various derivatives,such as search engines, social media, e-commerce, and other platforms, are not only networks and communicationplatforms, but also instruments of commodification, surveillance, and control by global digital companies that basedin the United States of America to millions of users around the world. From the results of the literature study andconceptual analysis of the processes of commodification, surveillance, and control, the authors conclude that claimsabout the democratic characteristics of the Internet are ideological in nature. The claim hides the economic andpolitical interests of the United States and its global digital companies. What the United States and these globaldigital companies have done has stripped away basic democratic values, such as respect for and protection ofhuman rights, freedom, and equality. From that conclusion, the authors suggest the need for openness andmultilateral globalism in Internet governance so that it is more friendly towards democratic values.Key words: Commodification, democracy, Internet, political economy, surveillance